Oracle E-business suite development and extensibility handbook [ - Passi, Anil; Ajvaz, Vladimir (McGraw-Hill, 2010)
"Transform your Oracle E-Business Suite infrastructure to suit enterprise requirements using the comprehensive development methods in this Oracle Press guide. Oracle E-Business Suite Development & Extensibility Handbook lays out each tool alongside reusable code and step-by-step examples. Learn how to create multiorg objects, integrate Java and PL/SQL, design custom user interfaces, and use Oracle Application Framework and Oracle Workflow. This detailed volume also explains how to work with Oracle XML Gateway, publish dynamic business intelligence reports, and tune your configuration."--Resource description p